1973
DOI: 10.1111/j.1365-2621.1973.tb02846.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postmortem Conditions on Certain Chemical, Morphological and Organoleptic Properties of Bovine Muscle

Abstract: Paired sides from U.S. Choice grade beef were aged immediately after slaughter at 2 and 16°C. Samples were removed from longissimus and semitendinosus at slaughter and at 1, 3 and 7 days postmortem for ATPase assay, phase microscopy, shear and organoleptic evaluation. Rib steaks from sides aged at 16°C for 1‐day postmortem were as tender as steaks from sides aged at 2°C for 7 days postmortem. Flavor development of rib steaks also was more rapid at 16°C than at 2°C. Tenderness of semitendinosus steaks was impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
5

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 29 publications
2
28
0
5
Order By: Relevance
“…Embora indesejável sob o ponto de vista sanitário, um pH elevado traz vantagens tecnológicas, aumentando a capacidade de retenção de água da carne e permitindo a elaboração de produtos mais nobres, como presunto cozido (HONIKEL, 1988;JUDGE, 1989;TERRA, 1998). Quando os músculos vermelhos são expostos ao frio em estágios anteriores ao estabelecimento do rigor mortis, há um aumento da força de contração tecidual (diminuição do comprimento do sarcômero), com conseqüente prejuízo da maciez da carne, fenômeno conhecido como encurtamento pelo frio (PARRISH et al, 1973;MARSH 1977;LOCHNER et al, 1980;JUDGE et al, 1989), o qual pode ser minimizado em carcaças grandes e pesadas, com adequada gordura de cobertura, pois a velocidade de resfriamento será menor (LOCHNER et al, 1980;MARSHALL, 1994). A carcaça da capivara é pequena e leve, se comparada a uma carcaça bovina.…”
Section: Resultsunclassified
“…Embora indesejável sob o ponto de vista sanitário, um pH elevado traz vantagens tecnológicas, aumentando a capacidade de retenção de água da carne e permitindo a elaboração de produtos mais nobres, como presunto cozido (HONIKEL, 1988;JUDGE, 1989;TERRA, 1998). Quando os músculos vermelhos são expostos ao frio em estágios anteriores ao estabelecimento do rigor mortis, há um aumento da força de contração tecidual (diminuição do comprimento do sarcômero), com conseqüente prejuízo da maciez da carne, fenômeno conhecido como encurtamento pelo frio (PARRISH et al, 1973;MARSH 1977;LOCHNER et al, 1980;JUDGE et al, 1989), o qual pode ser minimizado em carcaças grandes e pesadas, com adequada gordura de cobertura, pois a velocidade de resfriamento será menor (LOCHNER et al, 1980;MARSHALL, 1994). A carcaça da capivara é pequena e leve, se comparada a uma carcaça bovina.…”
Section: Resultsunclassified
“…Universidade Federal de Mato Grosso do Sul (UFMS), Campo Grande, MS, Brasil. fenômeno conhecido como cold shortening ou encurtamento pelo frio (PARRISH et al, 1973). O tecido muscular sofre maior encurtamento quando está em pré-rigor e na temperatura entre 2 e 37 o C, exceto na faixa de temperatura entre 14 e 19 o C, onde o encurtamento é mínimo (LOCKER & HAGYARD, 1963).…”
Section: Introductionunclassified
“…Similarly, Wheeler and Koohmaraie (1994) reported that the sarcomere length of ovine longissimus muscle decreased up to 24 h postmortem and then increased up to 14 d postmortem at 1 o C in a chill cooler. The myofibrillar fragmentation index (MFI) is a good indicator of the extent of proteolysis due to the vicinity of the Z-disc, and this parameter is affected by the storage periods and temperature Parrish et al, 1973). In many previous studies, MFI was used to evaluate and predict meat tenderness (Han et al, 1996), and a high positive correlation between MFI and shear force (p<0.0001, r= -0.53) in aged muscle was observed by Kim et al (2007).…”
Section: A Bmentioning
confidence: 99%